2022
DOI: 10.3390/sports10030028
|View full text |Cite
|
Sign up to set email alerts
|

Association between Functional Movement Screen Scores and Athletic Performance in Adolescents: A Systematic Review

Abstract: This study systematically reviews the literature examining the relationship between Fundamental Movement Screen (FMS©) scores and athletic performance in youth. We searched English-language papers on PubMed/MEDLINE, SportsDiscus, CINAHL, and EBSCO for the following inclusion criteria: Participants aged between 11 and 17 years, studies had to include the Functional Movement Screen© (FMS©) and at least one of the following performance outcomes, highlighted by athletic development models (i.e., long-term athletic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 51 publications
(156 reference statements)
1
8
0
1
Order By: Relevance
“…Indeed, as can be observed from the somatochart ( Figure 5 ), the distribution of the somatotype of female soccer players shifts towards the lower left quadrant, indicating a higher amount of body fat than males, regardless of their playing position. Conversely, the somatotype of the general population was endomorphic mesomorph regardless of sex, which may be due to less emphasis on non-optimal adipose tissue levels that can negatively impact athletic performance when elevated [ 8 ]. As in other sports [ 19 , 20 ], playing positions also play a discriminatory role in body composition, necessitating specific references for both sport and sex as well as playing position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, as can be observed from the somatochart ( Figure 5 ), the distribution of the somatotype of female soccer players shifts towards the lower left quadrant, indicating a higher amount of body fat than males, regardless of their playing position. Conversely, the somatotype of the general population was endomorphic mesomorph regardless of sex, which may be due to less emphasis on non-optimal adipose tissue levels that can negatively impact athletic performance when elevated [ 8 ]. As in other sports [ 19 , 20 ], playing positions also play a discriminatory role in body composition, necessitating specific references for both sport and sex as well as playing position.…”
Section: Discussionmentioning
confidence: 99%
“…Surface anthropometry serves as a valuable tool in understanding the morphological aspects of body composition, offering practical applications in fields ranging from sports science to clinical assessments. Indeed, body circumferences provide insights into body geometries and are influenced by both muscle and adipose tissue, particularly affecting endurance performance and movement quality [ 7 , 8 ]. Skinfolds, on the other hand, yield highly informative parameters for subcutaneous adipose tissue, a factor that negatively impacts endurance performance and mobility [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to Cook, issues at the foundational level can impact higher layers of movement capabilities. Previous research has found associations between functional movement and aspects such as physical performance, movement performance ( Fitton Davies et al, 2022 ; Zhang et al, 2022 ), and the occurrence of sports injuries ( Chorba et al, 2010 ; Dïnç & Arslan, 2020 ). However, the relationship between functional movement and movement performance lacks consensus ( Stapleton et al, 2021 ; Bennett et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…If a wushu athlete is restricted in many movements or unable to perform multi-joint movements on multiple planes, the limited motor function will seriously affect their performance [ 15 , 47 ]. Functional movement screen (FMS) is an effective tool to test the quality of athletes' exercise [ 48 ]. The body has 7 basic functional movement modes: squat, hurdle, straight lunge, active straight leg lift, shoulder flexibility, torso stability, and rotational stability [ 49 ].…”
Section: Introductionmentioning
confidence: 99%